Unequal Labour Market Impacts of COVID-19 in Sweden — But Not Between Women and Men - Pamela Campa; Jesper Roine; Svante Strömberg (Intereconomics)
Abstract So, when asked if men and women in the Swedish labour market have been differently affected by the COVID-19 pandemic, our overall conclusion would have to be “no”.